2015
DOI: 10.2341/13-325-l
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Anticaries Potential of Pit and Fissures Sealants Containing Amorphous Calcium Phosphate Using Synchrotron Microtomography

Abstract: The aim of this study was to analyze the anticaries potential of pit and fissure sealants containing amorphous calcium phosphate (ACP) by synchrotron microtomography. Bovine enamel blocks (4×4 mm; n=50) were selected through surface hardness (Knoop) analysis. Slabs were obtained through cross-sections taken 1 mm from the border of the enamel. Five indentations, spaced 100 μm apart, were made 300 μm from the border. Ten specimens were prepared for each tested material (Ultraseal XT plus TM, Aegis, Embrace, Vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(33 reference statements)
0
3
0
1
Order By: Relevance
“…Fluoride groups showed a positive rate of mineral gain, which was clearly visible in the outer layer of the enamel. The ACP group showed a loss of demineralization in the outer layer compared to the fluoride group, although it inhibition demineralization in the deep areas of the enamel, while the combination between (ACP and F) was highly effective in preventing demineralization [10].…”
Section: Variable Studied = the Amount Of Change In The Microhardness Between The Demineralized And The Sound Part Indication Of Differenmentioning
confidence: 81%
See 2 more Smart Citations
“…Fluoride groups showed a positive rate of mineral gain, which was clearly visible in the outer layer of the enamel. The ACP group showed a loss of demineralization in the outer layer compared to the fluoride group, although it inhibition demineralization in the deep areas of the enamel, while the combination between (ACP and F) was highly effective in preventing demineralization [10].…”
Section: Variable Studied = the Amount Of Change In The Microhardness Between The Demineralized And The Sound Part Indication Of Differenmentioning
confidence: 81%
“…The results of the Delben [10] study showed that ACP inhibited the demineralization in the deep areas of the enamel, while fluoride products had a greater effect in the surface areas of the enamel, while the combination of ACP and F remineralization factors was more effective In the prevention of demineralization. They evaluated the discontinuity probability of caries of ACPcontaining sealant using (SMG) synchrotron microtomography.…”
Section: Variable Studied = the Amount Of Change In The Microhardness Between The Demineralized And The Sound Part Indication Of Differenmentioning
confidence: 99%
See 1 more Smart Citation
“…promissora para a recuperação mineral da dentina e da camada híbrida na interface dentina-compósito, o que justifica a intensa atividade de pesquisa observada sobre este tema. contendo flúor e um cimento de ionômero de vidro modificado com resina)(99).Uma vez que a adição de partículas de CaP no compósito diminui sua resistência mecânica, diversas estratégias foram avaliadas para contornar este problema e permitir que estes compósitos possam ser utilizados em restaurações com elevada solicitação oclusal. Por exemplo, a associação de CaP com partículas 4.1 -Difractogramas das nanopartículas de DCPD sintetizadas Figura 4.2 -Imagens de microscopia eletrônica de transmissão mostrando as nanopartículas de DCPD funcionalizadas com TEGDMA (A) e não funcionalizadas (B) Figura 4.3 -Imagens de microscopia eletrônica de varredura mostrando os aglomerados de nanopartículas de DCPD funcionalizadas com TEGDMA (A) e não funcionalizadas (B).…”
unclassified